2018
DOI: 10.4049/jimmunol.1701597
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cells Lack Local Signals To Produce IFN-γ in the Skin during Leishmania Infection

Abstract: Resolution of leishmaniasis depends upon parasite control and limiting inflammation. CD4 Th1 cells are required to control parasites, whereas CD8 T cells play a dual role: they promote Th1 cell differentiation but can also increase inflammation at the site of infection as a consequence of cytolysis. Although CD8 T cells taken from leishmanial lesions are cytolytic, in this study, we showed that only a few CD8 T cells produced IFN-γ. Correspondingly, only low levels of IL-12 and/or IL-12 mRNA were present in le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
(69 reference statements)
3
23
0
Order By: Relevance
“…immune response against Leishmania braziliensis, with defined cytokine network, has been exhaustively reported [12][13][14][15][16][17]. Nevertheless, in some situations, a strong inflammatory response contributes to lesion progress and to exacerbation of the disease, which has been associated with cytotoxic events [9][10][11][12][13]. Recently, our group investigated the contributions of cytotoxic CD4 + T, CD8 + T, NK and NKT cells in the immune response in blood from CL patients before, during and after antimonial treatment, highlighting an important cytotoxic activity by CD4 + T and NKT cells, differently from classical-cytotoxic cells, as CD8 + T and NK cells [19].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…immune response against Leishmania braziliensis, with defined cytokine network, has been exhaustively reported [12][13][14][15][16][17]. Nevertheless, in some situations, a strong inflammatory response contributes to lesion progress and to exacerbation of the disease, which has been associated with cytotoxic events [9][10][11][12][13]. Recently, our group investigated the contributions of cytotoxic CD4 + T, CD8 + T, NK and NKT cells in the immune response in blood from CL patients before, during and after antimonial treatment, highlighting an important cytotoxic activity by CD4 + T and NKT cells, differently from classical-cytotoxic cells, as CD8 + T and NK cells [19].…”
Section: Plos Onementioning
confidence: 99%
“…Much is discussed about the events associated with the infection and its resolution and it has been suggested that CD4 + T lymphocytes mediate a protective immunity, whereas CD8 + T lymphocytes would have a pathological-cytotoxic role [9][10][11][12][13]. Nevertheless, a protective role for CD8 + T cells in the host immune response has already been clearly established [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…CD8 + T cells are considered important components of the inflammatory infiltrate present in the lesions ( Faria et al, 2009 ; Santos et al, 2013 ). However, its function has been discussed and recently it has been demonstrated that according to the functional profile, CD8 + T cells could play a beneficial (increasing the supply of IFN-γ) or harmful (by the predominance of cytotoxic activity) role ( Novais and Scott, 2015 ; Novais et al, 2018 ). Neutrophils have also been involved in the decrease in parasite load or in the amplification of macrophage infection ( Tacchini-Cottier et al, 2000 ; John and Hunter, 2008 ; Conceição et al, 2016 ).…”
Section: The Healing Process In Tlmentioning
confidence: 99%
“…Furthermore, using monoclonal antibody-based approach targeting the immune checkpoint molecules and/or immunoregulatory cytokines can be another avenue that can open possibilities for therapeutic intervention. PKDL infection is associated with lack of IFNγ producing signals in the skin [200] and administration of exogenous recombinant cytokine can potentially alleviate disease pathogenesis. Therefore, immunomodulatory therapy aiming to relieve the immunosuppressive microenvironment and instigate protective Th1 responses can be used together with chemotherapeutic regimens during VL treatment to prevent the emergence of PKDL.…”
Section: Immunology and Pkdlmentioning
confidence: 99%